Is Experiential Marketing Important for the Hospital? - ., Riskiyah; Hariyanti, T; Juhariah, S (KnE Life Sciences, 2018)
Experiential marketing is a hospital marketing to create a pleasant experience for patients, so that they would want to reuse the hospital services in the future. According to the inpatient satisfaction survey of UMM hospital, patients visiting hospitals usually complain about bathroom cleanliness, the food menu or the patient’s diet being less attractive, communication between doctor and patient or family being not so great. The existence of this complain indicates that experiential marketing conducted by Universitas Muhammadiyah Malang (UMM) Hospital has not been implemented properly. The purpose of this study is to reveal the experience of patients while undergoing inpatient at UMM hospital about experiential marketing. The method used in this research is qualitative phenomenology. In-depth interviews were conducted of eight informants considered to represent the patients on main class, class 1, class 2, class 3. In this study, only four of the five experiential marketing were found, that is, sense-, feel-, think-, and act marketing. Sense marketing obtained the patient’s experience of ease in finding information and directions. The feel marketing obtained that the officers provide services quickly when needed, the ease in the administration process, quiet and comfortable hospital environment, and cleanliness of rooms and bathrooms. The act marketing obtained the attention of paramedic to patients by giving the medicine on time. The think marketing obtained trust and distrust of the doctor. In conclusion, most of the experience of inpatients found that UMM Hospital has provided a fun and interesting experiential marketing. Keywords: patient experience, experiential marketing, inpatient